PENENTUAN PENURUNAN TEGANGAN BERDASARKAN MINIMUM SPANNING TREE PADA JARINGAN LISTRIK DISTRIBUSI PRIMER - Hardianto, Hardianto (Emitor, 2015)
Determination of the minimum spanning tree is widely used to solve optimization problems are problems that demand solutions minmum search. In the electricity distribution network, the minimum spanning tree (MST) is used to find the minimum cable length for the system to the power grid becomes more optimal. The use of a minimum weight minimum cable length can be used as a variable for calculating the voltage drop (voltage drop) of an electricity distribution network.Â  The method used in this research is the process of field observations and data processing. Field observations aims to take some of the coordinates of each pole on the electricity distribution network. While the data processing is done to create a geographic information system that is based on primary data in the form of a power pole coordinates data and secondary data along with the data in the form of electricity distribution networks. Furthermore, the results obtained by the minimum weight of the MST combined with existing data on the electricity distribution networks like cable cross-sectional area, the type of cable used, and the current through the tissue with voltage measurement results from the ends of the network to obtain results penurungan voltage (voltage drop) resulting from each feeder. Results (voltage drop) can be used as a basis for evaluating the electrical distribution network that has been existing, particularly in the City Bontang.